Dream Accounts in the Hebrew Bible and Ancient Jewish Literature - Quick, Laura 1987- (2018)
The study of dreams and their interpretation in the literary remains from antiquity have become increasingly popular access points to the phenomenological study of religious experience in the ancient world, as well as of the literary forms in which this experience was couched. This article considers the phenomenon of dreaming in the Hebrew Bible and ancient Jewish literature. I consider treatments of these dream accounts, noting the development in the methodological means by which this material has been approached, moving from source criticism, to tradition history, and finally to form-critical methods. Ultimately, I will argue that form criticism in particular enables scholars to discern shifts and developments across diachronic perspectives. Study of dream accounts is thus illuminating not only for the understanding of dream phenomena, but also for the development of apocalyptic and the method and means of early Jewish biblical interpretation.
Keywords: Antiquities; Apocrypha; Bible. Old Testament; Dead Sea Scrolls; Hermeneutics; Hebrew Bible; Jewish literature; Pseudepigrapha; Scholars; Apocalyptic; Dream interpretation; dream reports; Dreams; early Jewish biblical interpretation; Form Criticism; Source Criticism